a ) Nếu \(x=71\) \(\Rightarrow70=x-1\)
Thay \(70=x-1\) vào A , ta được :
\(A=x^5-\left(x-1\right)x^4-\left(x-1\right)x^3-\left(x-1\right)x^2-\left(x-1\right)x\)
\(=x^5-x^5+x^4-x^4+x^3-x^3+x^2-x^2+x\)
\(=x\)
\(=71\)
Vậy \(A=71\) tại \(x=71\)
b ) Ta có : \(x=35\)
\(\Rightarrow\left\{{}\begin{matrix}36=x+1\\37=x+2\\69=2x-1\\34=x-1\end{matrix}\right.\) ( * )
Thay ( * ) vào B , ta được :
\(B=x^5-\left(x+1\right)x^4+\left(x+2\right)x^3-\left(2x-1\right)x^2-\left(x-1\right)x+15\)
\(=x^5-x^5-x^4+x^4+2x^3-2x^3+x^2-x^2+x+15\)
\(=x+15\)
\(=35+15=50\)
Vậy \(B=50\) tại \(x=35\)